Detección de DNA de herpesvirus equino tipos 1 y 4 en mononucleares de sangre periférica y ganglio trigémino de equinos. Infección, latencia y una aproximación a la neuropatogénesis de la cepa circulante - Ruiz Sáenz, Julián; Góez, Yenny; López Herrera, Albeiro (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The infection with Equine Herpesvirus types 1 and 4 (EHV-1 and EHV-4) occurs at the upper respiratory tract. Soon after this takes place a primary cell associated viremia to peripheral blood mononuclear cells (PBMC, mainly on B and T lymphocytes), which allows the virus to reach other organic systems and production of abortions in the last third of gestation, neonatal foal death and neurological syndromes. After primary infection the animals remain latently infected for all the life. Because the presence of antibodies for EHV-1 and EHV-4 in plasma and serum of horses of two departments of Colombia was demonstrated, the objective of the present study as to demonstrate the presence of the viral genome in PBMC from horses diagnosed seropositive for EHV-1 and EHV-4, and in trigeminal ganglion of equines from a slaughterhouse of the Department of Antioquia. By means of a semi-nested PCR, the gene codifying for glycoprotein H (gH) of EHV-1 and gB of EHV-4 were amplified. In PBMC 28 and 19% of gH and of gB amplification were found, respectively; whereas in trigeminal ganglion 57.8 and 47.7% were amplified for gH and gB, respectively. With the aim of assessing whether the circulating strain in the department of Antioquia had a neuropathogenic potential, we amplified and sent to sequencing the gene that encodes the viral DNA polymerase, which could has a mutation that has been associated with neuropathogenic potential. We found that the circulating viral strain in Antioquia does not have such a mutation. The set of our results confirms that infection by EHV is present in the State of Antioquia, Colombia, and that there are equines latently infected which can be a source of infection for other susceptible horses.